Tantalus, a novel ASX-interacting protein with tissue-specific functions. - Dietrich, B; Moore, J; Kyba, M; dosSantos, G; McCloskey, F; Milne, T; Brock, H; Krause, H (2001)
The Drosophila trithorax- and Polycomb-group (trxG and PcG) proteins maintain activated and repressed transcriptional states at specific target gene loci. The Additional sex combs (Asx) gene is of particular interest as it appears to function in both protein complexes and yet its effects on target genes are more restricted. A novel protein, Tantalus (TAN), was identified in a yeast two-hybrid screen for ASX-interacting proteins that might confer tissue-specific ASX functions. TAN contains consensus nuclear localization sites and binds DNA in vitro. However, its subcellular localization varies in a tissue-specific fashion. In salivary glands, TAN is predominantly nuclear and associates with 66 euchromatic sites on polytene chromosomes, more than half of which overlap with ASX. These loci do not include the homeotic genes of the ANT and BX complexes bound by other PcG and trxG proteins. Rather, tan mutant defects are restricted to sensory organs. We show that one of these defects, shared by Asx, is genetically enhanced by Asx. Taken together, the data suggest that TAN is a tissue-specific cofactor for ASX, and that its activity may be partially controlled by subcellular trafficking.